Роль маркетингу у формуванні конкурентоспроможності промислових підприємств на міжнародних ринках: методологія GMC - Георгіца, В.О. (Економіка промисловості, 2025)
У статті розкрито роль маркетингу у формуванні міжнародної конкурентоспроможності промислових підприємств України. Обґрунтовано, що маркетингова спроможність є ключовим чинником успіху на зовнішніх ринках, особливо в умовах воєнного стану. Запропоновано авторську методологію Global Marketing Competitiveness (GMC), яка поєднує три індекси (Product & Technology, Marketing Strategy та Digital Promotion) із коефіцієнтом конвергенції на основі нормалізованих індикаторів та об’єктивного зважування. Методологія забезпечує комплексне оцінювання маркетингової конкурентоспроможності, орієнтоване на використання при стратегічному плануванні, у бенчмаркінгу, а також для підвищення ефективності управлінських рішень. The article examines the role of marketing in shaping the international competitiveness of industrial enterprises within the context of globalization and transformative changes in Ukraine's economy. It is substantiated that the marketing capability of an enterprise is a key factor in achieving success in foreign markets, especially under martial law and high demand dynamics. Based on a critical analysis of existing models for assessing competitiveness, the limitations in considering marketing factors are identified. In response to the existing methodological gap, the author proposes the Global Marketing Competitiveness (GMC) methodology, which enables a multi-level and structured assessment of the marketing component of a company's competitiveness. The structure of the GMC index and its components are presented: Product & Technology Index, Marketing Strategy Index, Digital Promotion Index, as well as the Convergence Factor that reflects the synergistic interaction between them. The proposed methodology combines analytical precision with practical applicability, making it suitable for strategic planning, benchmarking, evaluating investment attractiveness, and enhancing managerial decision-making in industrial companies. The advantages of GMC over traditional approaches are outlined: comprehensiveness, adaptability to industry specifics, measurability, and the ability for dynamic monitoring of marketing efficiency. The practical implementation of the GMC model enables enterprises to identify weak points, enhance brand positioning, optimize marketing investments, and improve export performance. Therefore, the GMC methodology serves as a universal diagnostic and strategic tool for enhancing the international marketing competitiveness of enterprises under conditions of high market turbulence and global uncertainty.